Induction of defense-related enzymes by Bacillus amyloliquefaciens DSBA-11 against bacterial wilt disease in tomato caused by Ralstonia solanacearum - narendra kumar*; GARIMA CHAUDHARY, DHANANJAY KUMAR YADAVA, DINESH SINGH* (Indian Phytopathology, 2016)
Bacterial wilt caused by Ralstonia solanacearum (Smith) Yabuuchi is a serious disease of tomato (Solanum lycopersicum L.) in tropical, subtropical and temperate areas of world including India. For management of the disease through biocontrol using microbes is an eco-friendly approach. Among various species of fungi and bacteria used as biocontrol agents, Bacillus spp. have potential to control plant diseases caused by fungi, bacteria and nematodes through mechanism of antibiosis and induced resistance in the plant. Antagonistic bacterium Bacillus amyloliquefaciens DSBA-11 was used as bioinducer and it was inoculated to the plant along with pathogen R. solanacearum UTT-25 at root zone of tomato cultivars Pusa Ruby (susceptible) and Arka Abha (resistant) under control conditions in Phytotron (temperature 28Â°C). The disease incidence was found minimum in Arka Abha (25.3%) treated with B. amyloliquefaciens DSBA-11 followed by Pusa Ruby (41.3%) after 30 days of inoculation. Induction of defense related enzyme such as phenylalanine ammonia lyase (PAL), polyphenol oxidase (PPO), peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) activities was studied in both tomato cultivars. The activities of PAL, PPO, POD, and SOD enzymes in both cultivars were increased by treating with DSBA-11 after pathogen inoculation. Catalase which is key H2O2 detoxifying enzymes was increased up to 72 h and later declined. This work supported the enhancement of antioxidant enzyme activities which could involve in suppression of the wilt disease.